The neonatologist and medical ethics - Oliveros Donohue, Miguel (2015)
In recent years we have seen in Peru that has attracted considerable interest in neonatology. The greatest advances are confined to hospitals in the capital, and primarily on Social Security, but the permanent care and doctors in overcoming provinces shown.